The Mismatch Between Mutual Fund Scale and Skill - SONG, YANG (Journal of Finance, 2020)
ABSTRACT I demonstrate that skill and scale are mismatched among actively managed equity mutual funds. Many mutual fund investors confuse the effects of fund exposures to common systematic factors with managerial skill when allocating capital among funds. Active mutual funds with positive factor‐related past returns thus accumulate assets to the point that they significantly underperform. I also show that the negative aggregate benchmark‐adjusted performance of active equity mutual funds is driven mainly by these oversized funds.